2019
DOI: 10.1021/acs.energyfuels.9b01348
|View full text |Cite
|
Sign up to set email alerts
|

Exergoeconomic Analysis of the Allam Cycle

Abstract: Greenhouse gas emissions from fossil fuel combustion is one of the main causes of global warming. Carbon capture, storage, and/or utilization consists of technologies and measures focused on diminishing anthropogenic emission of carbon dioxide (CO2), an important contributor to the greenhouse effect. One of the most promising methods for carbon capture is oxy-combustion, for which several innovative alternatives have been proposed in recent years. This paper evaluates a thermodynamic cycle known as the Allam c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Hervas et al [25] carried out a thermodynamic, exergetic and economic analysis of a 300 MWe power plant based on the Allam cycle. The used software is EBSILON Professional 13.…”
Section: Natural Gas-based Allam Cyclementioning
confidence: 99%
“…Hervas et al [25] carried out a thermodynamic, exergetic and economic analysis of a 300 MWe power plant based on the Allam cycle. The used software is EBSILON Professional 13.…”
Section: Natural Gas-based Allam Cyclementioning
confidence: 99%
“…Through comparison, they observed that the gas-fired Allam cycle exhibited higher exergy destruction in combustion compared to that in the combined gasifier and combustion in the coalfired Allam cycle. Rodri ́guez et al 28 conducted an exergoeconomic analysis of the Allam cycle and concluded that its efficiency and cost of electricity can compete with other lowemission technologies, albeit being higher than those of current combined cycle plants. Alenezi et al 29 performed an exergoeconomic analysis on the Allam cycle, driven by a combination of concentrated solar power and oxy-fuel combustion.…”
Section: Introductionmentioning
confidence: 99%